Long-term follow-up of buserelin-induced enteric neuropathy in rats - JÖNSSON, ANETTE (Mol Med Rep, 2016)
A few patients have been shown to develop severe abdominal pain and gastrointestinal dysmotility during treatment with gonadotropin-releasing hormone (GnRH) analogs. A rat model of enteric neuropathy has been developed by administration of the GnRH analog buserelin to rats. Loss of enteric neurons and ganglioneuritis throughout the gastrointestinal tract has been described, without other histopathological changes. The aim of the present study was to investigate the long-term effects of this rat model on body weight, and on morphology and inflammatory changes in the gastrointestinal tract. Rats were administered subcutaneous injections of buserelin or saline once daily for 5 days and allowed to recover for 3 weeks. This regimen was repeated four times. The rats were weighed weekly and were sacrificed 16 weeks after the fourth treatment. The bowel wall was measured by morphometry, and the presence of enteric neurons, mast cells, eosinophils and T-lymphocytes was evaluated. Buserelin-treated rats were shown to have a lower body weight at sacrifice, as compared with the controls (P<0.05). Compared with controls, buserelin treatment caused loss of myenteric neurons in the ileum and colon (P<0.01), a thinner circular muscle layer in ileum (P<0.05) and longitudinal muscle layer in colon (P<0.05), increased number of eosinophils in the submucosa of the ileum (P<0.05), and an increased number of T-lymphocytes in the submucosa and circular muscle layer of the fundus (P<0.01 and P<0.05, respectively) and circular muscle layer of the colon (P<0.05). Mast cells were equally distributed in the two groups. Thus, long-term follow-up of buserelin-induced enteric neuropathy reveals reduced body weight, loss of myenteric neurons, thinning of muscle layers, and increased numbers of eosinophils and T-lymphocytes in the gastrointestinal tract.